Analysis of Susceptibilities of Carbapenem Resistant Enterobacterales to Colistin in Intra-Abdominal, Respiratory and Urinary Tract Infections from 2015 to 2017 - Zhang H; Zhang J; Kang Y; Yang Q; Xu Y (Infection and Drug Resistance, 2020)
Hui Zhang,1 Jingjia Zhang,1 Yue Kang,2 Qiwen Yang,1 Yingchun Xu1 1Division of Microbiology, Peking Union Medical College Hospital, Peking Union Medical College, Chinese Academy of Medical Science, Beijing, People’s Republic of China; 2MRL Global Medical Affairs, MSD China, Shanghai, People’s Republic of ChinaCorrespondence: Qiwen Yang; Yingchun XuDivision of Microbiology, Peking Union Medical College Hospital, Peking Union Medical College, Chinese Academy of Medical Sciences, Beijing, People’s Republic of ChinaTel +86-10-69159763; Tel/ Fax +86-10-69159766Email yangqiwen81@vip.163.com; xycpumch@139.comPurpose: To evaluate the susceptibility rates of carbapenem-resistant (CR)-Enterobacterales strains from Chinese intra-abdominal infections (IAI), respiratory tract infections (RTI) and urinary tract infections (UTI) between 2015 and 2017 to colistin.Methods: In total, 7138 Enterobacterales including 1074 CR-Enterobacterales strains were isolated from IAI+UTI+RTI samples and collected in 21 hospitals across 7 regions of China. Antimicrobial susceptibilities were determined at a central laboratory using CLSI broth microdilution and interpretive standards.Results: From 2015 to 2017, E. coli (51.4%) and K. pneumoniae (30.0%) accounted for the majority of Enterobacterales isolated from IAIs, UTIs and RTIs. The percentage of CR strains within the species was highest for S. marcescens (27.9%), followed by K. pneumoniae (24.8%), P. mirabilis (22.6), K. oxytoca (19.5%), E. cloacae (17.7%), C. freundii (12.5%), K. aerogenes (11.0%) and lowest for E. coli (6.9%). Colistin susceptibilities were generally higher in CS than in CR isolates and were 83.5% for CR-E. coli, 88.6% for CR-K. pneumoniae, 79.2% for CR-E. cloacae and 87.5% for CR-K. aerogenes. For IAI and UTI isolates in particular, CR-E. coli and CR-K. pneumoniae showed a trend of decreasing susceptibility, which was especially noted for CR-E. coli in UTI isolates, and for both organisms in IAI isolates susceptibility dropped markedly in 2017.Conclusion: Colistin was a last resort antibiotics for empirical CR-Enterobacterales treatments, since especially the percentage of CR-K. pneumoniae was 30.0% of all IAI, UTI and RTI isolates, with an incidence of 24.8% CR strains, of which 88.6% were susceptible to colistin. Also other analyzed CR-Enterobacterales showed colistin susceptibilities of ≥ 80.0%. However, resistance rates of IAI derived CR-K. pneumoniae and CR-E. coli, and CR-K. pneumoniae UTI isolates to colistin increased between 2015 and 2017, which should further be closely monitored.Keywords: Enterobacterales, carbapenem, colistin, intra-abdominal infection, respiratory tract infection, urinary tract infection